Productivity and morphology of Ankole cattle in three livestock production systems in Uganda - Kugonza, Donald R.; Nabasirye, M.; Mpairwe, D.R.; Hanotte, Olivier H.; Okeyo Mwai, Ally (Cambridge University Press, 2011)
Phenotypic characterization is critical in breed improvement and conservation. To determine the performance and morphological features of Ankole cattle in three livestock production systems (LPS) of Uganda, 248 farms were studied. Height at withers (HW), heart girth (HG), body length (BL), ear length, horn length (HL), distance between horn tips (HS) and body weight (BW) were then measured on 120 bulls and 180 cows. Data were analysed using LPS (crop livestock, agropastoral, pastoral), county (Gomba, Kazo, Kiboga, Mawoggola, Nyabushozi) and sex (females, males) as main factors. In the results, age at sexual maturity was 23.6 ± 0.5 months for bulls and 22.7 ± 0.5 months for cows. Age at first calving was 33.2 ± 0.5 months, whereas calving interval was 12.9 ± 0.8 months. Lactation length differed between LPS (5.5 ± 0.4, 6.3 ± 0.3 and 7.4 ± 0.2 months in agropastoral, crop livestock and pastoral, respectively). Mean daily milk off take was 2.2 ± 0.1 kg/cow whereas preweaning calf survivability was 90.0 ± 6.5%. Sex and LPS significantly influenced HW, HL and HS. Positive correlations were observed between BW and HG, BL and HL. Correlation coefficients were much lower in females than in males, except for BW vs HG and BW vs HW. Results show wide variations both in performance and morphology suggesting that within breed selection scheme and/or management improvement may lead to productivity improvements.